2022
DOI: 10.1108/rpj-05-2022-0142
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cu-Ti dissimilar interface characteristics for wire arc additive manufacturing process

Abstract: Purpose The purpose of this research is to show the characteristics of a Cu–Ti dissimilar interface produced by a wire arc-based additive manufacturing process. The purpose of this research was to determine the viability of the Cu–Ti interface for the fabrication of functionally graded structures (FGS) using the wire arc additive manufacturing (WAAM) process. Design/methodology/approach This paper used the WAAM process with variable current vis-à-vis heat input to demonstrate multiple Ti-6Al-4V (Ti64) and C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Heat input is the prime controllable factor for penetration depth and dilution (Sarathchandra et al , 2020; Yin et al , 2020). WFS primarily decides the flow of arc current, which controls the heat input and wire melting rate (Mishra et al , 2023; Rodrigues et al , 2021; Wang et al , 2022). Under high WFS, current flow enhances the heat input and filler wire melting rate.…”
Section: Resultsmentioning
confidence: 99%
“…Heat input is the prime controllable factor for penetration depth and dilution (Sarathchandra et al , 2020; Yin et al , 2020). WFS primarily decides the flow of arc current, which controls the heat input and wire melting rate (Mishra et al , 2023; Rodrigues et al , 2021; Wang et al , 2022). Under high WFS, current flow enhances the heat input and filler wire melting rate.…”
Section: Resultsmentioning
confidence: 99%
“…The X-ray diffraction (XRD) technique were used to analyse the different phases formed at the interfaces of as-deposited wall. The dissimilar interfaces are found to be very critical due to formation of IMCs and unpredictable metallurgical and mechanical behaviour (Chen et al , 2020; Dharmendra et al , 2020; Mishra et al , 2022; Raj Paul et al , 2023; Senthil et al , 2021). Therefore, during all the metallurgical and mechanical analysis, the area of interest was abridged to the dissimilar interfaces, i.e.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…In addition, the interlayer can act as a stress sink, absorbing all the thermal stresses that develop at the interface, thereby maintaining its strength and integrity. Aligning with the scope, Mishra et al (2022) has used the CuSi material as interlayer between Ni718 and Ti64 alloys via WA-DED process. The authors reported the successful use of Cu as an interlayer between two highly dissimilar materials, as it was able to accommodate interfacial thermal stress while preventing the formation of detrimental IMCs at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, copper has good toughness and low hardness, significantly avoiding the occurrence of cracks in the repair process. 27 At the copper-Q235 interface, there exists a combination of Cu (s, s) and Fe (s, s), 28,29 while at the copper-TA1 base metal interface, a small number of Cu-Ti compounds can be found. In the titanium-steel contact region, a limited metallurgical reaction occurs, leading to the formation of Fe-Ti compounds in small quantities.…”
Section: Influence Mechanism Of Copper Interlayer On Wlar Of Ta1/q235...mentioning
confidence: 99%